PROTEOLYTIC ACTIVITY OF TISSUES CARP AND VOBLA UNDER THE INFLUENCE OF CADMIUM CHLORIDE - S. I. Kurbanova; N. I. Rabazanov; P. M. Nurmagomedova; Z. М. Magomedova; M. M. Magomedova (Юг России: экология, развитие, 2014)
The effect of CdCI2 (0.25 mg /l) on the proteolytic enzyme activities of the carp tissue are studied. The results confirm the involvement of cathepsin D and neutral protease in the development of the organism's response to the action of cadmium ions.